2017
DOI: 10.1002/ange.201702473
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Single Iron Atoms Anchored on N‐Doped Porous Carbon as an Efficient Electrocatalyst for the Oxygen Reduction Reaction

Abstract: The development of low-cost, efficient, and stable electrocatalysts for the oxygen reduction reaction (ORR) is desirable but remains ag reat challenge.H erein, we made ah ighly reactive and stable isolated single-atom Fe/N-doped porous carbon (ISA Fe/CN) catalyst with Fe loading up to 2.16 wt %. The catalyst showed excellent ORR performance with ah alf-wave potential (E 1/2 )o f0 .900 V, whicho utperformed commercial Pt/C and most non-precious-metal catalysts reported to date.B esides exceptionally high kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
312
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 437 publications
(327 citation statements)
references
References 34 publications
13
312
0
2
Order By: Relevance
“…1) which is denoted as M (C or A) N x C according to N coordination numbers. Alkaline electrolyte, commonly used in a typical ORR experiment for N-coordinated metal moieties, is chosen to evaluate the ORR performance 10,30 . The free energy diagram for ideal ORR catalyst model is illustrated in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) which is denoted as M (C or A) N x C according to N coordination numbers. Alkaline electrolyte, commonly used in a typical ORR experiment for N-coordinated metal moieties, is chosen to evaluate the ORR performance 10,30 . The free energy diagram for ideal ORR catalyst model is illustrated in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The X-ray photoelectron spectroscopy (XPS) spectrum of N 1s in Fig. 3g can be deconvoluted into four peaks corresponding to pyridinic-N, pyrrolic-N, Mg-Nx (corresponding to N a 38 of MgPc which bonds with Mg) and graphitic-N, respectively 30,39 . The Mg 1s and 2p spectrum in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The CoN 2 moieties outperform most previously reported nonprecious metal catalysts due to the strong interaction with peroxide . In a later study, FeN 4 moieties showed exceptional ORR performance ( E 1/2 = 0.900 V) in 0.1 m KOH solution . We employed our Fe–Co dual atoms catalyst in a fuel cell test, and the result revealed that it outperformed most reported Pt‐free catalysts in both H 2 /O 2 and H 2 /air conditions .…”
Section: Catalytic Performance Of Sacsmentioning
confidence: 90%
“…With these fascinating characteristics, SACs now rival nanoscale counterparts and continues to grow at an astonishing rate . Recently, we demonstrated the application of the SACs in heterogeneous catalysis ( Figure ), including oxygen reduction reaction (ORR), fuel cells, carbon dioxide (CO 2 ) reduction, selective hydrogenation and oxidation, and ammonia (NH 3 ) decomposition . For ORR, the CoN 2 moieties ( E 1/2 = 0.881 V) displayed improved ORR performance over commercial Pt/C (0.811 V) in 0.1 m KOH solution.…”
Section: Catalytic Performance Of Sacsmentioning
confidence: 99%
“…Indeedc atalyzed ORR is achieved with high efficiencya nd selectivity both in nature by cytochromecoxidases [1] and relatedo xidases [2] and in many fuel cells by preciousP t-based catalysts. [3] Recently,s ubstantial progress has been achievedi nt he electrochemical ORR with variousn on-precious Fe, [4,5] Co, [6,7] Mn, [8] Cu, [9][10][11] and Ni [11] catalysts.…”
mentioning
confidence: 99%